A New Take on Cataloging Popular Music Recordings. Issue 8 (16th November 2020) - Falk, Patricia; Lewis, David R.
Abstract: Cataloging popular music audio formats such as compact discs and LPs has always required different procedures from cataloging Western art music recordings. Bibliographic records and standards have changed during the past twenty years and catalogers have switched from using Anglo-American Cataloguing Rules (AACR2) to Resource Description and Access (RDA). This article will illustrate changes in popular music cataloging since the 2001 publication of Terry Simpkins' article "Cataloging Popular Music Recordings." Additional issues such as name authority and subject authority creation have been included, as well as new codes and MARC tags being used in bibliographic records.